Dosimetric advantages of intensity modulated radiation therapy in locally advanced lung cancer - John Boyle, MD; Brad Ackerson, MD; Lin Gu, MS; Chris R. Kelsey, MD (Advances in Radiation Oncology, 2017)
Purpose: Radiation therapy plays an essential role in the treatment of locally advanced lung cancer, but it inevitably leads to incidental and unnecessary dose to critical organs, including the lung, heart, and esophagus. Numerous radiation dose-volumetric parameters have been associated with increased risk of morbidity and mortality. The purpose of the present study is to quantify differences in normal tissue radiation exposure with intensity modulated radiation therapy (IMRT) compared with 3-dimensional conformal radiation therapy (3D-CRT). Methods and materials: Twenty-four consecutive patients with locally advanced lung cancer undergoing definitive IMRT were enrolled on a phase 1 protocol. For each patient, an optimized 3D-CRT plan was also designed. Plans were normalized in terms of planning target coverage with a standard dose of 60 Gy in 2-Gy fractions with a subset of patients also receiving elective nodal irradiation to a dose of 44 Gy in 2-Gy fractions. Normal tissue dosimetric comparisons were made for the lung, heart, and esophagus. Results: IMRT decreased incidental dose to the lungs, heart, and esophagus. For lung, both V20 Gy (21.5% vs 26.5%, P < .01) and mean lung dose (11.9 Gy vs 14.9 Gy, P < .01) were improved with IMRT without a corresponding increase in V5 Gy (P = .76). For heart, there was improvement in V5 (28.9% vs 33.7%, P < .01) but no difference in V30 Gy (9.8% vs 15.9%. P = .10). For esophagus, all dosimetric endpoints were improved (V20 Gy, V45 Gy, V60 Gy, mean dose). For example, V60 was 6.5% with IMRT compared with 21% with 3D-CRT (P < .01). Conclusions: IMRT significantly decreased unnecessary dose to critical organs with equivalent coverage of planning target volumes. IMRT may therefore improve the tolerability of therapy.